Future Trends in the Pharmacogenomics of Brain Disorders and Dementia: Influence of APOE and CYP2D6 Variants - Antón Álvarez; Verónica Couceiro; Susana Rodríguez; Ángela Casas; Margarita Alcaraz; Laura Nebril; Iván Tellado; Iván Carrera; Lola Corzo; Valter Lombardi; Adam McKay; Juan C. Carril; et al. (MDPI AG, 2010)
About 80% of functional genes in the human genome are expressed in the brain and over 1,200 different genes have been associated with the pathogenesis of CNS disorders and dementia. Pharmacogenetic studies of psychotropic drug response have focused on determining the relationship between variations in specific candidate genes and the positive and adverse effects of drug treatment. Approximately, 18% of neuroleptics are substrates of CYP1A2 enzymes, 40% of CYP2D6, and 23% of CYP3A4; 24% of antidepressants are substrates of CYP1A2 enzymes, 5% of CYP2B6, 38% of CYP2C19, 85% of CYP2D6, and 38% of CYP3A4; 7% of benzodiazepines are substrates of CYP2C19 enzymes, 20% of CYP2D6, and 95% of CYP3A4. 10-20% of Western populations are defective in genes of the CYP superfamily; and the pharmacogenomic response of psychotropic drugs also depends on genetic variants associated with dementia. Prospective studies with anti-dementia drugs or with multifactorial strategies have revealed that the therapeutic response to conventional drugs in Alzheimer's disease is genotype-specific. The disease-modifying effects (cognitive performance, biomarker modification) of therapeutic intervention are APOE-dependent, with APOE-4 carriers acting as the worst responders (APOE-3/3 > APOE-3/4 > APOE-4/4). APOE-CYP2D6 interactions also influence the therapeutic outcome in patients with dementia.